Preparation method and application of ceramic antibacterial and antiviral additive

CN117837606BActive Publication Date: 2025-02-25JIANGXI HUANXING VALLEY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310543490.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-15
Publication Date
2025-02-25
Estimated Expiration
2043-05-15

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a ceramic antibacterial and anti-virus additive, the preparation method comprising the following steps: (1) preparing nano zirconium phosphate; (2) preparing polydopamine; (3) preparing polydopamine-modified nano zirconium phosphate; (4) preparing polydopamine-modified nano zirconium phosphate-diatomite composite; (5) polydopamine-modified nano zirconium phosphate-diatomite composite loading silver nitrate. By loading silver nitrate with polydopamine-modified nano zirconium phosphate-diatomite composite, silver ions are not easy to agglomerate in the layered structure of diatomite and polydopamine-modified nano zirconium phosphate, and at the same time, it can also avoid the destruction of metal silver ions melting into the glass phase during high-temperature firing, and polydopamine-modified nano zirconium phosphate can well adsorb bacteria, and can cooperate with silver ions to kill bacteria, thereby improving its antibacterial performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of antibacterial technology, and in particular to a preparation method and application of a ceramic antibacterial and anti-virus additive. Background Art

[0002] Ceramics is called the mother of inorganic materials. It is a kind of inorganic non-metallic material made of natural or synthetic compounds through forming and high-temperature sintering. It is the general name of pottery and porcelain. It has the superior properties of low density, high strength, corrosion resistance, high hardness, high temperature resistance and good chemical stability. Countries around the world, especially developed countries, attach great importance to the development and utilization of new ceramic materials. In particular, the new ceramic materials developed in recent years have been widely used in aerospace, biology, semiconductors, bionics, computers, automobiles, medical care, military and other fields. With the improvement of people's living standards and the strengthening of health awareness, people gradually realize that the health of the body is closely related to the quality of the living environment. People's demand for antibacterial ceramics is becoming more and more intense. People will consider implanting antibacterial ceramics into homes and public places to effectively avoid the spread of bacteria and diseases and reduce cross infection.

[0003] Common antibacterial materials on the market generally use inorganic antibacterial agents such as silver, zinc, copper or silver-zinc composites. They mainly use inorganic materials as carriers to load silver, copper, zinc and other ions or elements, and achieve the antibacterial purpose by the precipitation of metal ions into bacteria and killing bacteria.

[0004] CN107265862A discloses a method for preparing a silver ion antibacterial ceramic, comprising: (1) beating a raw material of ceramic clay into a slurry with a pulping machine, pouring the slurry into a mixer for mixing and mixing uniformly, and injecting the slurry into a ceramic mold to produce a ceramic clay blank; (2) adding an oxide containing silver to a ceramic glaze and mixing uniformly to produce a silver ion ceramic glaze containing a bactericidal effective component; (3) rubbing the ceramic glaze containing silver ions on the ceramic clay blank to produce a ceramic clay blank containing a silver ion ceramic glaze containing a bactericidal effective component; (4) spraying the ceramic clay blank containing a silver ion ceramic glaze containing a bactericidal effective component with a photocatalyst having an antibacterial effect; (5) placing the ceramic clay blank rubbed with the glaze produced in step (4) into a kiln for sintering to produce a silver ion antibacterial ceramic. The ceramic produced by the method has good antibacterial performance and can effectively inhibit bacterial growth. However, the silver ion antibacterial agent in the invention is released quickly, resulting in a short antibacterial life of the material, and its components are easily destroyed during high temperature, thereby reducing its antibacterial ability. Summary of the invention

[0005] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to provide a ceramic antibacterial and disinfectant additive with good antibacterial effect.

[0006] To achieve the above-mentioned purpose, the present invention provides a ceramic antibacterial and bactericidal additive. By using a polydopamine-modified nano zirconium phosphate-diatomaceous earth composite to load silver ions, the silver ions are not easy to agglomerate in the layered structure of diatomaceous earth and the polydopamine-modified nano zirconium phosphate, and at the same time, the metal silver ions can be prevented from melting into the glass phase and being destroyed during the high-temperature firing process. The polydopamine-modified nano zirconium phosphate can adsorb bacteria well and can synergistically kill bacteria with silver ions, thereby improving its antibacterial performance.

[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0008] A ceramic antibacterial and antiviral additive, and a preparation method thereof, comprising the following steps:

[0009] (1) Preparation of nano zirconium phosphate; (2) Preparation of polydopamine; (3) Preparation of polydopamine-modified nano zirconium phosphate; (4) Preparation of polydopamine-modified nano zirconium phosphate-diatomaceous earth composite; (5) Polydopamine-modified nano zirconium phosphate-diatomaceous earth composite loaded with silver nitrate.

[0010] Preferably, the ceramic antibacterial and antiviral additive, and its preparation method comprises the following steps:

[0011] (1) Preparation of nano zirconium phosphate: zirconium oxychloride octahydrate and nitric acid aqueous solution are mixed; phosphoric acid aqueous solution is added dropwise, and after the addition is completed, heating and stirring are performed to obtain a reaction solution; the reaction solution is then subjected to ultrasonication, allowed to stand, and centrifugation to collect a precipitate, and the precipitate is dried and ground to obtain nano zirconium phosphate;

[0012] (2) Preparation of polydopamine: preparing a dopamine hydrochloride aqueous solution, adding a Tris buffer, then heating for reaction, centrifuging, filtering and collecting the residue, washing the residue with water and drying to obtain polydopamine;

[0013] (3) Preparation of polydopamine-modified nano zirconium phosphate: After ultrasonic treatment of the nano zirconium phosphate obtained in step (1) in hydrochloric acid, the polydopamine obtained in step (2) is added, and then an aqueous solution of ammonium persulfate is added dropwise, reacted, centrifuged, and solids are collected. The solids are dried and ground to obtain polydopamine-modified nano zirconium phosphate;

[0014] (4) Preparation of polydopamine-modified nano zirconium phosphate-diatomite composite: mixing polyvinyl alcohol aqueous solution and glutaraldehyde and stirring, adding thioglycolic acid, heating to react, adding diatomite and the polydopamine-modified nano zirconium phosphate obtained in step (3), continuing heating to react, cooling after the reaction, filtering, collecting the filter cake, washing the filter cake with water and drying to obtain the polydopamine-modified nano zirconium phosphate-diatomite composite;

[0015] (5) dispersing the polydopamine-modified nano zirconium phosphate-diatomaceous earth composite obtained in step (4) in water, adding fatty alcohol polyoxyethylene ether AEO-9 and silver nitrate, filtering, washing, drying and grinding after the reaction is completed to obtain a ceramic antibacterial and antiviral additive.

[0016] Further preferably, the ceramic antibacterial and antiviral additive, and its preparation method comprises the following steps:

[0017] (1) Preparation of nano zirconium phosphate: zirconium oxychloride octahydrate and 0.5-1 mol / L nitric acid are mixed; 1-1.5 mol / L phosphoric acid is added dropwise, and after the addition is completed, the mixture is heated to 85° C. and stirred at 300-400 rpm for 5-8 hours to obtain a reaction solution; the reaction solution is then subjected to ultrasonic reaction at 700-900 W for 5-15 minutes, and after the reaction is completed, the reaction solution is allowed to stand for 20-24 hours; the precipitate is collected by centrifugation, and the precipitate is dried at 60-80° C. for 10-12 hours, and then ground to obtain nano zirconium phosphate;

[0018] (2) Preparation of polydopamine: prepare a 20-30 wt% dopamine hydrochloride aqueous solution and adjust the pH value to 8-9, add a Tris buffer with a pH value of 7-9 and mix well, then heat to 30-50°C for reaction for 1-2 hours, centrifuge, filter and collect the residue, wash the residue with water 2-3 times and freeze-dry at -45 to -40°C for 24 to 48 hours to obtain polydopamine;

[0019] (3) Preparation of polydopamine-modified nano zirconium phosphate: The nano zirconium phosphate obtained in step (1) is added to 0.5-1 mol / L hydrochloric acid and ultrasonically treated at 30-60 W and 150-200 Hz for 10-20 min, the polydopamine obtained in step (2) is added at a stirring speed of 600-800 rpm, and then 40-60 mL of 40-50 wt% ammonium persulfate aqueous solution is added at a rate of 1-2 drops / second. After the addition is complete, the mixture is reacted at room temperature for 8-10 h. After the reaction is completed, the mixture is centrifuged to collect the solid matter, and the solid matter is dried at 70-80°C for 10-12 h, and then ground to obtain polydopamine-modified nano zirconium phosphate;

[0020] (4) Preparation of polydopamine-modified nano zirconium phosphate-diatomite composite: at room temperature, 3-5 wt% polyvinyl alcohol aqueous solution was mixed with glutaraldehyde, stirred at 1500-2500 rpm for 1-2 h, thioglycolic acid was added, heated to 60-80° C. for reaction for 2-3 h, diatomite and the polydopamine-modified nano zirconium phosphate obtained in step (3) were added, and the mixture was heated to 100-120° C. for reaction for 20-30 min, cooled to room temperature, filtered, and the filter cake was collected. The filter cake was washed with water for 2-3 times and then dried at 60-80° C. for 6-8 h to obtain a polydopamine-modified nano zirconium phosphate-diatomite composite;

[0021] (5) dispersing the polydopamine-modified nano zirconium phosphate-diatomaceous earth composite obtained in step (4) in water, adding fatty alcohol polyoxyethylene ether AEO-9 and silver nitrate in turn, stirring at room temperature at a speed of 600-800 rpm for 1-2 hours, filtering and washing with water 2-3 times, drying at 60-80° C. for 6-8 hours, and grinding into powder to obtain a ceramic antibacterial and disinfectant additive.

[0022] Preferably, in step (1), the usage ratio of zirconium oxychloride octahydrate, nitric acid and phosphoric acid is 3-5 g: 50-100 mL: 150-300 mL.

[0023] Preferably, in step (2), the ratio of the dopamine hydrochloride aqueous solution to the Tris buffer is 2-4:1-3.

[0024] Preferably, in step (3), the dosage ratio of nano zirconium phosphate, hydrochloric acid, polydopamine and ammonium persulfate aqueous solution is 2-5 g: 100-200 mL: 5-8 g: 40-60 mL.

[0025] Preferably, in step (4), the dosage ratio of the polyvinyl alcohol aqueous solution, glutaraldehyde, thioglycolic acid, diatomaceous earth, and polydopamine-modified nano-zirconium phosphate is 200-300 mL: 5-6 g: 10-12 g: 30-40 g: 2-5 g.

[0026] Preferably, in step (5), the dosage ratio of the polydopamine-modified nano zirconium phosphate-diatomaceous earth composite, water, fatty alcohol polyoxyethylene ether AEO-9, and silver nitrate is 1-3 g: 200-300 mL: 5-10 mL: 8-10 g.

[0027] Zirconium phosphate silver-loaded antibacterial agent is a commonly used inorganic antibacterial agent. However, although the existing zirconium phosphate silver-loaded antibacterial agent has a certain antibacterial effect, after being applied to ceramics, the zirconium phosphate silver-loaded antibacterial agent has no promoting effect on the mechanical properties of the ceramics. At the same time, when the amount of zirconium phosphate silver-loaded antibacterial agent added is increased in order to improve the antibacterial effect, the thermal shock resistance of the ceramics will also be reduced. Therefore, it is very necessary to develop a zirconium phosphate silver-loaded antibacterial agent that can simultaneously promote the mechanical properties and antibacterial properties of ceramics.

[0028] Nano zirconium phosphate is a spherical structure of two-dimensional layered cations, each layer of which is composed of a phosphate group bonded to a zirconium atom, and the phosphate groups alternate above and below the plane of the zirconium atom. Zirconium is octahedrally coordinated with six oxygen atoms, of which three different zirconium atoms are bonded to three oxygen atoms of each phosphate group. Polydopamine contains nitrogen atoms, which can provide active sites for reaction with polydopamine. By reacting with nano zirconium phosphate, polydopamine-modified nano zirconium phosphate with better adsorption effect is obtained. By further compounding with diatomaceous earth with adsorption capacity, more active sites of diatomaceous earth can be exposed, silver ions can be better loaded, and the binding and wrapping ability with silver ions can be enhanced. In addition, silver ions are not easy to agglomerate between the layered structure of diatomaceous earth and polydopamine-modified nano zirconium phosphate. Nanomaterials with good dispersion can make the mechanical properties of the material more excellent. The carrier can better adsorb bacteria, and at the same time, it can also avoid the destruction of metal silver ions melting into the glass phase during high-temperature firing, and can synergistically sterilize with silver ions, thereby improving its antibacterial properties.

[0029] The inventors use polydopamine modified nano zirconium phosphate-diatomaceous earth composite as a carrier of silver ions, which can provide more adsorption channels and better load silver ions. At the same time, its large specific surface area is conducive to improving sintering activity and improving the thermal shock resistance of the blank.

[0030] The present invention also discloses an application of the ceramic antibacterial and antiviral additive, and the specific method is: add 25-30 parts by mass of albite, 45-55 parts by mass of kaolin, 20-25 parts by mass of quartz sand, 5-8 parts by mass of the ceramic antibacterial and antiviral additive, and 5-10 parts by mass of volcanic stone powder into a ball mill, wet-mill for 20-30 hours, pass through a 200-300 mesh sieve, and dry at 80-100°C for 8 hours to obtain a mixture; press the mixture into a shape at 80-85MPa to obtain a dry embryo; place the dry embryo in a firing kiln for sintering, and cool to room temperature after sintering to obtain a ceramic containing the ceramic antibacterial and antiviral additive.

[0031] Preferably, the sintering temperature is 1100-1300° C., and the sintering time is 8-10 h.

[0032] Compared with the prior art, the present invention has the following beneficial effects: the inventor adopts the polydopamine-modified nano zirconium phosphate-diatomite composite as a carrier of silver ions, which can provide more adsorption channels and better load silver ions; at the same time, its large specific surface area is conducive to improving the sintering activity and improving the thermal shock resistance of the blank; and silver ions are not easy to agglomerate between the layered structure of diatomite and the polydopamine-modified nano zirconium phosphate, and the nano material with good dispersion can make the mechanical properties of the material more excellent. The carrier can better adsorb bacteria and can cooperate with silver ions to kill bacteria, and at the same time, it can also avoid the destruction of metal silver ions melting into the glass phase during high-temperature firing, thereby improving its antibacterial performance. DETAILED DESCRIPTION

[0033] To avoid redundancy, the items used in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods unless otherwise specified.

[0034] The sources of some raw materials used in the present invention are as follows:

[0035] Zirconium oxychloride octahydrate, density is 1.91g / cm 3 , Condis Chemical (Hubei) Co., Ltd.

[0036] Dopamine hydrochloride, CAS No. 62-31-7, ignition residue ≤ 0.05%, melting point 248-250℃, Shanghai Fusheng Industrial Co., Ltd.

[0037] Diatomaceous earth, 325 mesh, content of 95%, specific surface area of ​​40-65℃, Lingshou County Baiyi Mineral Products Processing Plant.

[0038] Sodium feldspar, 325 mesh, Na2O content is 7-15%, SiO2 content is 65%, Al2O3 content is 16-25%, density is 2.61g / cm 3 , Lingshou County Yang’s Mineral Products Co., Ltd.

[0039] Kaolin, 325 mesh, density 2.56g / cm 3 , the silicon dioxide content is 46.64%, Lingshou County Baiyi Mineral Products Processing Plant.

[0040] Quartz sand, 140 mesh, density 2.65g / cm 3 , Wuhan Longlin Chemical Co., Ltd.

[0041] Volcanic stone powder, content is 99%, 600 mesh, hardness is 5, wear rate is 0.01%, Lingshou County Shengfei Product Processing Factory.

[0042] Polyvinyl alcohol, content is 99%, item number is 001, Lingshou County Jianshi Mineral Powder Factory.

[0043] Example 1

[0044] A method for preparing a ceramic containing a ceramic antibacterial and antiviral additive comprises the following steps: adding 300g of albite, 550g of kaolin, 250g of quartz sand, 80g of the ceramic antibacterial and antiviral additive, and 100g of volcanic stone powder into a ball mill, wet-milling for 25h, passing through a 250-mesh sieve, and drying at 80°C for 8h to obtain a mixture; pressing the mixture into a shape at 85MPa to obtain a dry embryo; placing the dry embryo in a firing kiln and sintering at 1215°C for 8h, and cooling to room temperature after sintering to obtain the ceramic containing the ceramic antibacterial and antiviral additive.

[0045] The preparation method of the ceramic antibacterial and antiviral additive comprises the following steps:

[0046] (1) Preparation of nano zirconium phosphate: 50 g of zirconium oxychloride octahydrate and 1000 mL of 0.5 mol / L nitric acid were mixed; 3000 mL of 1 mol / L phosphoric acid was added dropwise at a rate of 2 drops / second. After the addition was completed, the mixture was heated to 85°C and stirred at 350 rpm for 6 hours to obtain a reaction solution; the reaction solution was then subjected to ultrasonic reaction at 800 W for 10 minutes, and after the reaction was completed, the mixture was allowed to stand for 24 hours; the precipitate was collected by centrifugation, and the precipitate was dried at 65°C for 12 hours, and then ground to obtain nano zirconium phosphate;

[0047] (2) Preparation of polydopamine: 300 mL of 30 wt% dopamine hydrochloride aqueous solution was prepared and the pH value was adjusted to 8, 200 mL of Tris buffer with a pH value of 8 was added and mixed evenly, and then heated to 40°C for reaction for 2 h, centrifuged, filtered and collected, the residue was washed with water 3 times and freeze-dried at -40°C for 40 h to obtain polydopamine;

[0048] (3) Preparation of polydopamine-modified nano zirconium phosphate: 5 g of the nano zirconium phosphate obtained in step (1) was added to 200 mL of 1 mol / L hydrochloric acid and ultrasonically treated at 50 W and 180 Hz for 15 min. 7.5 g of the polydopamine obtained in step (2) was added at a stirring speed of 700 rpm, and then 50 mL of a 50 wt% ammonium persulfate aqueous solution was added at a rate of 1 drop / second. After the addition was completed, the reaction was allowed to proceed at room temperature for 10 h. After the reaction was completed, the reaction was centrifuged to collect the solids, which were dried at 75°C for 12 h, and ground to obtain polydopamine-modified nano zirconium phosphate;

[0049] (4) Preparation of polydopamine-modified nano zirconium phosphate-diatomite composite: At room temperature, 300 mL of 5 wt% polyvinyl alcohol aqueous solution was mixed with 6 g of glutaraldehyde, stirred at 2000 rpm for 1 h, 11.8 g of thioglycolic acid was added, heated to 70° C. for reaction for 3 h, 35.4 g of diatomite and 4.8 g of the polydopamine-modified nano zirconium phosphate obtained in step (3) were added, and the mixture was heated to 110° C. for reaction for 30 min, cooled to room temperature, filtered, and the filter cake was collected. The filter cake was washed with water 3 times and dried at 80° C. for 6 h to obtain a polydopamine-modified nano zirconium phosphate-diatomite composite;

[0050] (5) Disperse 3 g of the polydopamine-modified nano zirconium phosphate-diatomaceous earth composite obtained in step (4) in 250 mL of water, add 10 mL of fatty alcohol polyoxyethylene ether AEO-9 and 9.6 g of silver nitrate in turn, stir at room temperature at 700 rpm for 1 h, filter and wash with water 3 times, dry at 80 ° C for 6 h, and grind into powder to obtain a ceramic antibacterial and disinfectant additive.

[0051] Comparative Example 1

[0052] A method for preparing a ceramic containing a ceramic antibacterial and antiviral additive comprises the following steps: adding 300g of albite, 550g of kaolin, 250g of quartz sand, 80g of the ceramic antibacterial and antiviral additive, and 100g of volcanic stone powder into a ball mill, wet-milling for 25h, passing through a 250-mesh sieve, and drying at 80°C for 8h to obtain a mixture; pressing the mixture into a shape at 85MPa to obtain a dry embryo; placing the dry embryo in a firing kiln and sintering at 1215°C for 8h, and cooling to room temperature after sintering to obtain the ceramic containing the ceramic antibacterial and antiviral additive.

[0053] The preparation method of the ceramic antibacterial and antiviral additive comprises the following steps:

[0054] (1) Preparation of nano zirconium phosphate: 50 g of zirconium oxychloride octahydrate and 1000 mL of 0.5 mol / L nitric acid were mixed; 3000 mL of 1 mol / L phosphoric acid was added dropwise at a rate of 2 drops / second. After the addition was completed, the mixture was heated to 85°C and stirred at 350 rpm for 6 hours to obtain a reaction solution; the reaction solution was then subjected to ultrasonic reaction at 800 W for 10 minutes, and after the reaction was completed, the mixture was allowed to stand for 24 hours; the precipitate was collected by centrifugation, and the precipitate was dried at 65°C for 12 hours, and then ground to obtain nano zirconium phosphate;

[0055] (2) Preparation of nano zirconium phosphate-diatomite composite: At room temperature, 300 mL of 5 wt% polyvinyl alcohol aqueous solution was mixed with 6 g of glutaraldehyde, stirred at 2000 rpm for 1 h, 11.8 g of thioglycolic acid was added, heated to 70° C. for reaction for 3 h, 35.4 g of diatomaceous earth and 4.8 g of nano zirconium phosphate obtained in step (1) were added, and the mixture was heated to 110° C. for reaction for 30 min, cooled to room temperature, filtered, and the filter cake was collected. The filter cake was washed with water 3 times and dried at 80° C. for 6 h to obtain a nano zirconium phosphate-diatomite composite;

[0056] (3) Disperse 3 g of the nano zirconium phosphate-diatomaceous earth composite obtained in step (2) in 250 mL of water, add 10 mL of fatty alcohol polyoxyethylene ether AEO-9 and 9.6 g of silver nitrate in sequence, stir at room temperature at 700 rpm for 1 h, filter and wash with water 3 times, dry at 80 ° C for 6 h, and grind into powder to obtain a ceramic antibacterial and disinfectant additive.

[0057] Comparative Example 2

[0058] A method for preparing a ceramic containing a ceramic antibacterial and antiviral additive comprises the following steps: adding 300g of albite, 550g of kaolin, 250g of quartz sand, 80g of the ceramic antibacterial and antiviral additive, and 100g of volcanic stone powder into a ball mill, wet-milling for 25h, passing through a 250-mesh sieve, and drying at 80°C for 8h to obtain a mixture; pressing the mixture into a shape at 85MPa to obtain a dry embryo; placing the dry embryo in a firing kiln and sintering at 1215°C for 8h, and cooling to room temperature after sintering to obtain the ceramic containing the ceramic antibacterial and antiviral additive.

[0059] The preparation method of the ceramic antibacterial and antiviral additive comprises the following steps:

[0060] (1) Preparation of nano zirconium phosphate: 50 g of zirconium oxychloride octahydrate and 1000 mL of 0.5 mol / L nitric acid were mixed; 3000 mL of 1 mol / L phosphoric acid was added dropwise at a rate of 2 drops / second. After the addition was completed, the mixture was heated to 85°C and stirred at 350 rpm for 6 hours to obtain a reaction solution; the reaction solution was then subjected to ultrasonic reaction at 800 W for 10 minutes, and after the reaction was completed, the mixture was allowed to stand for 24 hours; the precipitate was collected by centrifugation, and the precipitate was dried at 65°C for 12 hours, and then ground to obtain nano zirconium phosphate;

[0061] (2) Disperse 3 g of the nano zirconium phosphate obtained in step (1) in 250 mL of water, add 10 mL of fatty alcohol polyoxyethylene ether AEO-9 and 9.6 g of silver nitrate in turn, stir at room temperature at 700 rpm for 1 h, filter and wash with water 3 times, dry at 80 ° C for 6 h, and grind into powder to obtain a ceramic antibacterial and disinfectant additive.

[0062] Comparative Example 3

[0063] A method for preparing a ceramic containing a ceramic antibacterial and antiviral additive comprises the following steps: adding 300g of albite, 550g of kaolin, 250g of quartz sand, 80g of the ceramic antibacterial and antiviral additive, and 100g of volcanic stone powder into a ball mill, wet-milling for 25h, passing through a 250-mesh sieve, and drying at 80°C for 8h to obtain a mixture; pressing the mixture into a shape at 85MPa to obtain a dry embryo; placing the dry embryo in a firing kiln and sintering at 1215°C for 8h, and cooling to room temperature after sintering to obtain the ceramic containing the ceramic antibacterial and antiviral additive.

[0064] The preparation method of the ceramic antibacterial and antiviral additive comprises the following steps:

[0065] Disperse 3 g of diatomaceous earth in 250 mL of water, add 10 mL of fatty alcohol polyoxyethylene ether AEO-9 and 9.6 g of silver nitrate in turn, stir at 700 rpm at room temperature for 1 hour, filter and wash with water 3 times, dry at 80°C for 6 hours, grind into powder to obtain a ceramic antibacterial and disinfectant additive.

[0066] Comparative Example 4

[0067] A method for preparing a ceramic containing a ceramic antibacterial and antiviral additive comprises the following steps: adding 300g of albite, 550g of kaolin, 250g of quartz sand, 80g of the ceramic antibacterial and antiviral additive, and 100g of volcanic stone powder into a ball mill, wet-milling for 25h, passing through a 250-mesh sieve, and drying at 80°C for 8h to obtain a mixture; pressing the mixture into a shape at 85MPa to obtain a dry embryo; placing the dry embryo in a firing kiln and sintering at 1215°C for 8h, and cooling to room temperature after sintering to obtain the ceramic containing the ceramic antibacterial and antiviral additive.

[0068] The ceramic antibacterial and anti-virus additive is silver nitrate.

[0069] Test Example 1

[0070] Antibacterial performance test: The ceramic antibacterial and antiviral additives prepared in Example 1 and Comparative Examples 1-4 were tested for antibacterial performance according to the method in Appendix A of GB / T21510-2008 "Test Methods for Antibacterial Performance of Nano-inorganic Materials". The test strains were Escherichia coli ATCC 8099 and Staphylococcus aureus ATCC 6538. The test steps were as follows:

[0071] 1) Cultivate the dried bacteria of Escherichia coli and Staphylococcus aureus to the third generation, dilute the fresh bacterial moss after culturing for 24 hours to 105 cfu / mL with phosphate buffer to obtain a prefabricated bacterial suspension; 2) Weigh 0.5g of the ceramic antibacterial and disinfectant additive, 95mL of PBS buffer containing 0.1% Tween 80 and 5mL of the prefabricated bacterial suspension in a conical flask and mix them evenly; 3) Cultivate the above mixture at a constant temperature of 37℃±1℃ and 150rpm for 24 hours; 4) After completion, dilute the test sample solution 50 times and take 1mL The sample solution is inoculated on a sterile plate, and each sample solution is inoculated on 3 plates in parallel; 5) Pour the nutrient agar medium dissolved at 45℃ onto the plate; 6) After the agar medium solidifies, turn the plate over and place it in a 37℃ constant temperature incubator for 48 hours. After completion, count the viable bacteria culture (blank samples are subjected to the same operation). The actual number of recovered strains of the sample is calculated by the plate count method to calculate the number of colonies and then multiply it by the dilution factor. The antibacterial rate (R) is calculated based on the actual number of recovered strains. The antibacterial rate calculation formula is as follows. The average value of three tests is taken as the antibacterial rate of the sample;

[0072] R=(AB) / A×100%

[0073] R is the antibacterial rate, %;

[0074] A is the average colony count recovered after the antibacterial test of the blank group, cfu / mL (the total number of bacterial colonies contained in each milliliter of sample);

[0075] B is the average number of colonies recovered after antimicrobial testing in the experimental group, cfu / mL;

[0076] The test results are shown in Table 1:

[0077] Table 1 Test results of antibacterial properties of ceramic antibacterial and antiviral additives

[0078]

[0079] It can be seen from the experimental results in Table 1 that the ceramic antibacterial and antiviral additive prepared in Example 1 has the best antibacterial performance. The difference between Example 1 and other comparative examples is that polydopamine-modified nano zirconium phosphate-diatomaceous earth composite is added to load silver nitrate. The possible reason for this phenomenon is that the polydopamine-modified nano zirconium phosphate-diatomaceous earth composite, as a carrier of silver ions, can provide more adsorption channels, can better load silver ions, and enhance the ability to combine and wrap with silver ions. The carrier can better adsorb bacteria, and at the same time, it can also avoid the destruction of metal silver ions by melting into the glass phase during high-temperature firing, and can synergistically kill bacteria with silver ions, thereby improving its antibacterial performance.

[0080] Test Example 2

[0081] Bending strength test: Referring to ISO 6872-2015 "Dental Ceramic Materials", the bending strength of the ceramics containing ceramic antibacterial and antiviral additives prepared in Example 1 and Comparative Examples 1-4 was tested by a three-point bending method using a universal material testing machine AGS-10kNG (Shimadzu, Japan). The loading rate was 0.5 mm / min, the sample thickness was 1.2 mm, the width was 4 mm, and the sample span was 12 mm. The calculation formula is as follows: σ = 3Pl / 2wb 2

[0082] σ is the fracture strength of ceramic, MPa;

[0083] P is the failure load, MPa;

[0084] l is the specimen span, mm;

[0085] w is the width of the specimen, mm;

[0086] b is the sample thickness, mm;

[0087] The same sample was tested 10 times and the average value was taken. The test results are shown in Table 2:

[0088] Table 2 Test results of flexural strength of ceramics containing ceramic antibacterial and antiviral additives

[0089] Flexural strength(MPa) Example 1 276 Comparative Example 1 268 Comparative Example 2 254 Comparative Example 3 226 Comparative Example 4 187

[0090] It can be seen from the experimental structure in Table 2 that the ceramic containing the ceramic antibacterial and disinfectant additive prepared in Example 1 also has the best mechanical properties. The possible reason for this phenomenon is that the polydopamine-modified nano zirconium phosphate-diatomaceous earth composite is used as a carrier of silver ions, which can provide more adsorption channels and better load silver ions. At the same time, its large specific surface area is conducive to improving the sintering activity, and silver ions are not easy to agglomerate between the layered structure of diatomaceous earth and the polydopamine-modified nano zirconium phosphate, which can avoid the destruction of metallic silver ions by melting into the glass phase during high-temperature firing. The nanomaterial with good dispersibility improves the mechanical properties of the material.

Claims

1. A method for preparing a ceramic antibacterial and antiviral additive, characterized in that: The method comprises the following steps: (1) preparing nano zirconium phosphate: mixing zirconium oxychloride octahydrate and 0.5-1 mol / L nitric acid; adding 1-1.5 mol / L phosphoric acid dropwise, heating to 85°C, stirring at 300-400 rpm for 5-8 hours to obtain a reaction solution; then subjecting the reaction solution to ultrasonic reaction at 700-900 W for 5-15 minutes, and allowing the reaction solution to stand for 20-24 hours after the reaction is completed; collecting the precipitate by centrifugation, drying the precipitate at 60-80°C for 10-12 hours, and grinding to obtain nano zirconium phosphate; the dosage ratio of zirconium oxychloride octahydrate, nitric acid, and phosphoric acid is 3-5 g: 50-100 mL: 150-300 mL; (2) Preparation of polydopamine: prepare a 20-30wt% dopamine hydrochloride aqueous solution and adjust the pH value to 8-9, add a Tris buffer solution with a pH value of 7-9 and mix well, then heat to 30-50°C for reaction for 1-2h, centrifuge, filter and collect the residue, wash the residue with water 2-3 times and freeze-dry at -45~-40°C for 24~48h to obtain polydopamine; The ratio of dopamine hydrochloride aqueous solution to Tris buffer is 2-4:1-3; (3) Preparation of polydopamine-modified nano zirconium phosphate: The nano zirconium phosphate obtained in step (1) is added to 0.5-1 mol / L hydrochloric acid and ultrasonically treated at 30-60 W and 150-200 Hz for 10-20 min, the polydopamine obtained in step (2) is added at a stirring speed of 600-800 rpm, and then 40-60 mL of 40-50 wt% ammonium persulfate aqueous solution is added at a rate of 1-2 drops / second. After the addition is complete, the mixture is reacted at room temperature for 8-10 h. After the reaction is completed, the mixture is centrifuged to collect the solids, and the solids are dried at 70-80°C for 10-12 h, and then ground to obtain polydopamine-modified nano zirconium phosphate; the dosage ratio of nano zirconium phosphate, hydrochloric acid, polydopamine, and ammonium persulfate aqueous solution is 2-5 g: 100-200 mL: 5-8 g: 40-60 mL; (4) Preparation of polydopamine modified nano zirconium phosphate-diatomite composite: at room temperature, 3-5wt% polyvinyl alcohol aqueous solution and glutaraldehyde are mixed, stirred at 1500-2500rpm for 1-2h, thioglycolic acid is added, heated to 60-80℃ for reaction for 2-3h, diatomite and polydopamine modified nano zirconium phosphate obtained in step (3) are added, and the mixture is heated to 100-120℃ for reaction for 20-30min, cooled to room temperature, filtered, and the filter cake is collected. The filter cake is washed with water for 2-3 times and then dried at 60-80℃ for 6-8h to obtain polydopamine modified nano zirconium phosphate-diatomite composite; the amount ratio of polyvinyl alcohol aqueous solution, glutaraldehyde, thioglycolic acid, diatomite, and polydopamine modified nano zirconium phosphate is 200-300mL: 5-6g: 10-12g: 30-40g: 2-5g; (5) The polydopamine-modified nano zirconium phosphate-diatomite complex obtained in step (4) is dispersed in water, and fatty alcohol polyoxyethylene ether AEO-9 and silver nitrate are added in sequence, stirred at room temperature at a speed of 600-800 rpm for 1-2 hours, filtered and washed with water for 2-3 times, dried at 60-80° C. for 6-8 hours, and ground into powder to obtain a ceramic antibacterial and disinfectant additive; the amount ratio of the polydopamine-modified nano zirconium phosphate-diatomite complex, water, fatty alcohol polyoxyethylene ether AEO-9, and silver nitrate is 1-3 g: 200-300 mL: 5-10 mL: 8-10 g.

2. A ceramic antibacterial and antiviral additive, characterized in that: The ceramic antibacterial and antiviral additive is prepared by the preparation method of claim 1.

3. An application of the ceramic antibacterial and antiviral additive as claimed in claim 2 in ceramics, characterized in that: The specific method is: add 25-30 parts by mass of albite, 45-55 parts by mass of kaolin, 20-25 parts by mass of quartz sand, 5-8 parts by mass of ceramic antibacterial and disinfectant additives, and 5-10 parts by mass of volcanic stone powder into a ball mill, wet ball mill for 20-30 hours, pass through a 200-300 mesh sieve, and dry at 80-100°C for 8 hours to obtain a mixture; press the mixture into shape at 80-85MPa to obtain a dry embryo; place the dry embryo in a firing kiln for sintering, and cool to room temperature after sintering to obtain a ceramic containing the ceramic antibacterial and disinfectant additive.

Citation Information

Patent Citations

  • Preparation method of anti-bacterial silver-ion ceramic

    CN107265862A

  • High temperature resistant inorganic antimicrobial material and preparation method thereof

    CN101461374A

  • Silver-loaded zirconium phosphonate synergetic antibacterial agent as well as preparation method and application thereof

    CN103229783A